Identifying orthopaedic surgeons of the future: the inability of some medical students to achieve competence in basic arthroscopic tasks despite training: a randomised study. - Alvand, A; Auplish, S; Khan, T; Gill, H; Rees, J (2011)
The aim of this study was to investigate the effect of training on the arthroscopic performance of a group of medical students and to determine whether all students could be trained to competence. Thirty-three medical students with no previous experience of arthroscopy were randomised to a 'Trained' or an 'Untrained' cohort. They were required to carry out 30 episodes of two simulated arthroscopic tasks (one shoulder and one knee). The primary outcome variable was task success at each episode. Individuals achieved competence when their learning curve stabilised. The secondary outcome was technical dexterity, assessed objectively using a validated motion analysis system. Six subjects in the 'Untrained' cohort failed to achieve competence in the shoulder task, compared with one in the 'Trained' cohort. During the knee task, two subjects in each cohort failed to achieve competence. Based on the objective motion analysis parameters, the 'Trained' cohort performed better on the shoulder task (p < 0.05) but there was no significant difference for the knee task (p > 0.05). Although specific training improved the arthroscopic performance of novices, there were individuals who could not achieve competence despite focused training.These findings may have an impact on the selection process for trainees and influence individual career choices.